2012
DOI: 10.3390/toxins4121451
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II and Non-MHC Class II Genes Differentially Influence Humoral Immunity to Bacillus anthracis Lethal Factor and Protective Antigen

Abstract: Anthrax Lethal Toxin consists of Protective Antigen (PA) and Lethal Factor (LF), and current vaccination strategies focus on eliciting antibodies to PA. In human vaccination, the response to PA can vary greatly, and the response is often directed toward non-neutralizing epitopes. Variable vaccine responses have been shown to be due in part to genetic differences in individuals, with both MHC class II and other genes playing roles. Here, we investigated the relative contribution of MHC class II versus non-MHC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Similarly, markers in HLA-DRB5 were found to be associated with elevated antibody response. In our own previous study in this population [37], carriage of three haplotypes in this region ( DRB1*1501-DQA1*0102-DQB1*0602 , DRB1*0101-DQA1*0101-DQB1*0501 , and DRB1*0102-DQA1*0101-DQB1*0501) were all significantly associated with lower AbPA levels in the longitudinal analyses [18]. Recently in an animal study [37], MHC class II locus has been associated with high antibody titers to a component of anthrax toxin, lethal factor whereas non-MHC class loci were discovered to influence antibody titers to protective antigen.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, markers in HLA-DRB5 were found to be associated with elevated antibody response. In our own previous study in this population [37], carriage of three haplotypes in this region ( DRB1*1501-DQA1*0102-DQB1*0602 , DRB1*0101-DQA1*0101-DQB1*0501 , and DRB1*0102-DQA1*0101-DQB1*0501) were all significantly associated with lower AbPA levels in the longitudinal analyses [18]. Recently in an animal study [37], MHC class II locus has been associated with high antibody titers to a component of anthrax toxin, lethal factor whereas non-MHC class loci were discovered to influence antibody titers to protective antigen.…”
Section: Discussionmentioning
confidence: 76%
“…A key experiment in this regard was to compare the impact of STI challenge on survival and the control of bacterial load in mice, all on a C57BL/6 background and lacking expression of endogenous murine MHC class II heterodimers but differing in expression of specific HLA-DR or HLA-DQ alleles. The background C57BL/6 strain is considered one that mounts a low antibody response to anthrax PA and LF [37]. We found that HLA-DR15 transgenics (expressing the HLA-DRB1*1501 allele) were the most susceptible to challenge, echoing the results of human AVA HLA-DRB1*1501 + vaccinees [38].…”
Section: Discussionmentioning
confidence: 86%
“…In seeking an improved understanding of the interaction between B. anthracis and protection by the human immune system, a key question has been the impact of immunogenetic heterogeneity at the population level [36]; work in mouse models has suggested that, as expected, both MHC and non-MHC polymorphisms are influencing these factors [37]. With respect to human vaccination, there is evidence of reduced immune responsiveness to PA in individuals with the DRB1*1501/DQB1*0602 haplotype [38].…”
Section: Discussionmentioning
confidence: 99%
“…In seeking an improved understanding of the interaction between B. anthracis and protection by the human immune system, a key question has been the impact of immunogenetic heterogeneity at the population level [ 45 ]. Work in mouse models has suggested that, as expected, both MHC and non-MHC polymorphisms influence these factors [ 46 ]. With respect to human vaccination, there is evidence of reduced immune responsiveness to PA in individuals with the DRB1*1501/DQB1*0602 haplotype [ 47 ].…”
Section: Discussionmentioning
confidence: 88%